Emission of enteric methane in cold dry season in sudanians peulh zebus in west africa - (:unkn) unknown (My University, 2022)
- In Africa, ruminants contribute strongly to the greenhouse gas emissions such as enteric methane(eCH4). A few models for estimating eCH4 have been developed in the tropics. However, no direct measurement ofeCH4 emissions in cattle has been made and reported in West Africa. The objective of the present study is toevaluate in vivo eCH4 emissions in Sudanese Peulh Zebu during the cold dry season (November 2021 - February2022). For this purpose, 10 steers aged 27±1.87 months with a live weight (LW) of 138.82±15.23 kg (i.e. 0.56Tropical Livestock Unit - TLU) were used for direct measurements with the GreenFeed at CIRDES (Burkina Faso).Measurements of eCH4 emissions were coupled with those of ingestion based on two levels of rangeland foragesupply: 3.5% and 2.5% of LW for four weeks. Mean eCH4 and voluntary forage intake emissions were comparedbetween forage supply levels using Student's paired t-test (significance level, 5%). The results show that nosignificant difference (p=0.10) was observed between the average daily amounts of voluntary dry matter intake(VDMI) between the two levels of supply. Variation in grass supply induced no significant difference for eCH4 ing/kg MSiV (p=0.72) and in g/kg P0.75 (p=0.61). The level of ingestion and eCH4 emissions remained constant overthe season. This work will be continued during the hot dry and rainy seasons to account for seasonal variability inthe quality of rangeland forage resources in pastoral livestock systems in West Africa.
Keywords: African Research